Factors affecting the bird community on Gaya Island, Sabah, Malaysia - Emily A. Gilbert (2019)
Gaya Island is well known as one of the hot spots for tourist destinations in Sabah. This island harbours both terrestrial and marine wildlife that attracts the tourist in visiting this island. To date, there are only a few studies have been conducted on the impact of the factors influencing the bird community in Gaya Island as the bird act as an important indicator for the health of the island's ecosystem. The purpose of this study is to obtain primary data for Sabah Park to be used as guideline to conserve the bird community in that island in reference to the influencing factor namely the anthropogenic noise and vegetation factors. Hence, this study aims to determine the effect of the influencing factors namely the anthropogenic noise and vegetation on the bird community in Gaya Island. The null hypothesis proposed in this study is that the anthropogenic noise and vegetation does not significantly affect the bird community in Gaya Island. The data collection was conducted for six months in three of the selected sampling sites within the island. The methods that were being used were solely point count sampling, noise measurement and circular plot sampling. Meanwhile, diversity indexes, Spearman's correlation and Mann-Whitney U were used to analyse the obtained data. A total number of 511 individuals from 25 species and 16 families were recorded during the survey. The Shannon_Wiener index showed that the diversity of birds is slightly higher in high anthropogenic noise categories (H'=2.524) as compared to the low anthropogenic noise categories (H'=2.498) but there was no significant difference of species diversity between two noise categories. Interestingly, according to the result from Mann-Whitney U test, there were eight species of birds showed significant different in terms of abundance at the species level of birds between both types of noise categories (p<0.05). In addition, the result of the Spearman's correlation analysis showed that the anthropogenic noise is negatively correlated with the species richness and abundance of birds and it is very significant (r=-0.054, p=0.000). However, for the tree composition, the result showed that there is no significant correlation between the basal area, stem density and tree diversity with the species richness and abundance of bird in that island. Therefore, the findings from this study showed the anthropogenic noise does play a role in affecting the bird community in Gaya island while there was no statistically significant impact of the basal area, stem density and tree diversity towards the bird community in that island. Nonetheless, further study still needed to be conducted at the other parts of Gaya island in order to get a representative data on the effects of these influencing factors to bird population in that island.